Efficacy of Autologous Platelet Rich Plasma For Treatment of Diabetic Foot Ulcer (Journal of Dhaka Medical College, 2024)
Background: Diabetic foot ulcer (DFU) is a common complication of long standing uncontrolled diabetes mellitus. There  are different types of treatment commonly practiced among the clinicians to treat DFU. Among them, autologous platelet rich plasma (PRP) application is getting popularity day by day throughout the western world.Methodology: It was a prospective, randomized, controlled study that was carried out among 40 DFU patients in the Department of Surgery, Dhaka Medical College Hospital. Among them, 20 patients were treated by autologous PRP and another 20 patients were treated by conventional method. They were followed up for 12 weeks period. Data collected from  the participants were analyzed to compare the healing rate among two groups.Result: In PRP treated ulcers, healing rate was significantly faster and better in comparison to conventionally treated ulcers. After 10th weeks follow up, in PRP group 14 ulcers were completely healed whereas in control group,4 ulcers were completely healed. On the contrary, 3 ulcers in control group showed further deterioration. At the end of 12th weeks follow  up, 19 ulcers in PRP group were completely healed whereas 13 ulcers in control group were completely healed. In PRP group no patient showed any complication during treatment, whereas in control group 7 patients experienced local complications.Conclusion: Treatment of diabetic foot ulcer with autologous platelet rich plasma results in faster and better ulcer healing in comparison to conventional treatment. PRP accelerates the healing rate and keep the ulcer area safe from external pathogens. Hence, autologous PRP is a better selection for DFU treatment.J Dhaka Med Coll. 2023; 32(1) : 38-42